Appraisal of Linear Type Traits in Simmental Cows Reared on High Altitude of Eastern Turkey - Olcay Guler; Mete Yanar; Abdulkerim Diler; Recep Aydın; Rıdvan Kocyigit (Journal of Agricultural Sciences)
The study was carried out to investigate the magnitude of non-genetic factors influencing linear type traits and to estimate phenotypic correlations among these traits in Simmental cows. The 16 linear type traits were recorded for 148 Simmental cows reared in a private farm in Eastern Turkey. A statistical model used in this research included fixed effects of stage of lactation, parity, season at time of classification and classifier. The age at time of classification was included to the statistical model as co-variable. Parity, stage of lactation, season at time of classification and classifier effect was significant (P<0.01-0.05) for chest width, angularity, teat placement side view, body depth. Parity, stage of lactation, season at time of classification effect was significant (P<0.01-0.05) for rear leg rear view, rump width, suspensory ligament and udder depth. Linear and quadratic effects of age at time of classification were also significant (P<0.01-0.05) for rump width, rump angle, teat placement rear view, foot angle, suspensory ligament and udder depth. Phenotypic correlations among linear type traits were in low to medium range.